Pengaturan Penggunaan Frasa Menghadap Dan Berhadapan Dalam Pembuatan Akta Notaris - Bagazi, Firhan Umar; Artha, I Gede (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 8 No 01 (2023)DO - 10.24843/AC.2023.v08.i01.p9, 2023)
The writing of this article aims for reveal and analyze the arrangement of the phrase facing and dealing in legislation, especially the Notarian Law and which phrase is more appropriate to use in the case of making an authentic deed by a notary. This article discusses legal issues, namely empty norms using normative legal research methods as well as statute  and conceptual approaches, the legal source materials in this article come from fundamental, second to third legal materials. This study reflect  that there are no rules governing the use of the phrase facing or facing in the making of a notary deed, in the regulation and definition of the UUJN (P) there is zero definition regarding the use of the phrase. This phrase is very important because each phrase places the notary in a different position where in the opposite phrase the notary is assumed to be able to face each other not within his area of ??office, while the phrase facing indicates that the notary is passive in that it is the appearers who come to meet the notary in the area of ??his office. So that clarity regarding the use of this phrase is very necessary considering the role of the notary who must be passive and the arrangement of this phrase can also protect the notary from possible involvement or problems in the deed he made.